Challenges of protecting minors in cyberspace between the absence of digital identity and the fragility of the law - Hassan, Karzan Izzat (Journal of Legal and Political Studies, 2024)
In the last decade information technology went through an unprecedented revolution, which made possible interdependence in multiple sectors, including communications, but it also shaped a new reality of interdependence of individuals with the society thereon. These advances have, in turn, allowed the emergence of new phenomena which is termed as cyberspace. In a great deal, it is a space which is characterized, inter alia, by its rapid expansion. However, the use of technology in the cyberspace for such aims has rendered the virtual space a dangerous habitat. It is also very important to note that such acts are cybercrimes, and they are treated as a rather specific type. So, there is room for the development of the new code, which would aim at combating cybercrime, which would ensure the proper functioning of the cyberspace, and also make it possible to punish perpetrators of those activities, for example, those who abused the children. Hence, Iraq has an obligation to develop an effective and proper legislative mechanism in relation to this issue Keywords: Juvenile protection, cyberspace, digital identity, law
Keywords: Juvenile protection; cyberspace; digital identity; law